Narcissism, Spiritual Pride, and Original Sin - Halligan, Fredrica R. (Journal of religion and health, 1997)
Narcissism has roots in childhood and a broad impact on society. Parental abuse, neglect, or exploitation result in unmet emotional needs that leave low self-esteem and patterns of longing for affirmation. When these needs are not gratified, interpersonal conflict ensues. At the extreme, torture, wars, and other conflagrations can be seen to have roots in narcissism, which is thus construed as the psychological explanation for what religion defines as original sin. The cold, dark pain of narcissistic woundedness comprises an abyss in the soul. Spiritual resources, including mysticism and surrender to divine love, may offer deep healing for those wounds.